ANALYSIS RELATES TO THE IMPACT OF FINANCIAL PERFORMANCE ON BANKING STOCK PRICES - Hedwigis Esti Riwayati; Aviliani Aviliani (International Journal of Economy, Education and Entrepreneurship, 2022)
This study aims to analyze the effect of return on assets, return on equity and earnings per share on stock prices. This research is an explanatory research using quantitative methods. The sample used in this study is a state-owned banking company that meets the criteria by using the purposive sampling method. This study uses secondary data in the form of financial statements obtained from the Indonesia Stock Exchange for state-owned banks. The data analysis technique in this study used descriptive statistical analysis and panel data regression analysis using Eviews 12. The results showed that return on assets and earnings per share had a significant positive effect on stock prices, return on equity had no effect on bank stock prices for state-owned banking company